Seismic performance of reinforced concrete beam-column joints strengthened with NSM steel bars and NSM CFRP strips. (May 2022) - Hashemi, Seyed Meisam; Tajmir Riahi, Hossein
Abstract: Three strengthening methods for RC beam-column joints using NSM steel bars and NSM CFRP strips were experimentally evaluated by cyclic loading. These methods increase joints capacity and prevent the plastic hinge formation near the column while try to minimize destructive task on floor slab. Strengthened specimens and a control specimen of RC beam-column joint from an intermediate moment-resisting frame were constructed on one-half scale and subjected to cyclic loading according to ACI 374.1-05 simultaneously with a constant column's axial load to study their seismic behavior. Experimental results indicated that the proposed methods could increase joints capacity up to 30% compared to the control specimen and two of them improve joints ductility by removing the plastic hinge from the joint core. In addition, the energy dissipation of the retrofitted specimens was increased up to 100% and they experienced less pinching hysteresis behavior. The debonding of CFRP strips in one of specimens showed that the penetration depth of CFRP strips into the core should be increased to avoid this phenomenon. In addition, the anchorage method of the added steel rebar inside the joint core worked well and forces were transferred to the column properly.